“Kaan-mîn-yenîñe” a resignificação simbólica da liderança religiosa entre os Waiwai - Rodrigues, David Batista (2018)
This dissertation aims to understand how it is built and manifestation of the local pastors alterity among the Waiwai: the "kaan-mîn-yen^ñe", mainly in the Indigenous Community of Anauá, taking into account 1. The processes of cultural mediation that originated to the Waiwai people. 2. Research on the cultural traits derived from Christian doctrine and the history of the Waiwai meeting with Western culture. 3. Analyze comparatively the symbolic, diacritical and social organization elements of this position among the people.